ANALYSIS OF CHINESE TOURISTS’ PERCEPTION ON NORTH SULAWESI - Monica, Yocom .; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Tourism sectors in Indonesia play an important role in national economic earning. A major problem of Indonesian tourism in the perspective of global tourism is that the competitiveness of Indonesian tourism sector was low and generally found that Manado is still perceived differently among Chinese tourists. The purpose of this research is to explore the perception of Chinese tourists on destination image North Sulawesi. The researcher used method Correspondence Analysis - Perceptual mapping as the tool for the data analysis to analyze Chinese tourists’ perception on North Sulawesi, this research is conducted by distributing questionnaires to 100 respondents. The result found that China tourist perception on Manado is still not yet integrated, so the government must be able to improve the primary element of tourism such as transportation system, cultural facilities, hotels and resorts, tourist attractions, and product varieties by promoting the tourism places. Events in North Sulawesi must be made as attractive and as friendly as possible to all kinds of tourists’ age categories. Keywords: tourism, perception, Chinese tourists, correspondence analysis